A reverse translational study on the effect of rituximab, rituximab plus belimumab, or bortezomib on the humoral autoimmune response in SLE. (17th January 2020) - van Dam, Laura S; Osmani, Zgjim; Kamerling, Sylvia W A; Kraaij, Tineke; Bakker, Jaap A; Scherer, Hans U; Rabelink, Ton J; Voll, Reinhard E; Alexander, Tobias; Isenberg, David A; van Kooten, Cees; Teng, Y K Onno
Abstract: Objectives: SLE is a severe autoimmune disease characterized by autoreactive B cells and IC formation, which causes systemic inflammation. B cell–targeted therapy could be a promising treatment strategy in SLE patients; nevertheless, randomized clinical trials have not always been successful. However, some groups have demonstrated beneficial effects in severe SLE patients with off-label rituximab (RTX) with belimumab (BLM), or bortezomib (BTZ), which targeted different B cells subsets. This study assembled sera from SLE cohorts treated with RTX+BLM ( n = 15), BTZ ( n = 11) and RTX ( n = 16) to get an in-depth insight into the immunological effects of these therapies on autoantibodies and IC formation. Methods: Autoantibodies relevant for IC formation and the avidity of anti-dsDNA were determined by ELISA. IC-mediated inflammation was studied by complement levels and ex vivo serum-induced neutrophil extracellular trap formation. Results: Reductions in autoantibodies were observed after all approaches, but the spectrum differed depending upon the treatment. Specifically, only RTX+BLM significantly decreased anti-C1q. Achieving seronegativity of ≥1 autoantibody, specifically anti-C1q, was associated with lower disease activity. In all SLE patients, the majority of anti-dsDNA autoantibodies had low avidity. RTX+BLM significantly reduced low-, medium- and high-avidity anti-dsDNA, while RTX and BTZ only significantly reduced medium avidity. IC-mediated inflammation, measured by C3 levels and neutrophil extracellular trap formation, improved after RTX+BLM and RTX but less after BTZ. Conclusion: This study demonstrated the impact of different B cell–targeted strategies on autoantibodies and IC formation and their potential clinical relevance in SLE.